2013
DOI: 10.1371/journal.pmed.1001524
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Postpartum Hemorrhage of Prophylactic Oxytocin (10 IU) by Injection by Community Health Officers in Ghana: A Community-Based, Cluster-Randomized Trial

Abstract: Cynthia Stanton and colleagues conducted a cluster-randomized controlled trial in rural Ghana to assess whether oxytocin given by injection by community health officers at home births was a feasible and safe option in preventing postpartum hemorrhage. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 13 publications
0
47
0
9
Order By: Relevance
“…Manufacturers could play a role in accelerating programmatic implementation in low-resource settings by developing such a TTI with greater specificity for oxytocin, by improving flexibility in packaging such that TTIs could be affixed to either OIU packages or oxytocin vials (which are more widely available and cost less), and by further elucidating the relationship between temperature exposure and API under various conditions. Oxytocin remains the drug of choice for prevention of postpartum hemorrhage, and OIU has been demonstrated to reduce postpartum hemorrhage by half in home deliveries in Ghana 8 . The data from this simulation study provide some guidance to program managers as to how this effective intervention might be rolled out at scale and how oxytocin could be used at peripheral health facilities without cold-chain capacity.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Manufacturers could play a role in accelerating programmatic implementation in low-resource settings by developing such a TTI with greater specificity for oxytocin, by improving flexibility in packaging such that TTIs could be affixed to either OIU packages or oxytocin vials (which are more widely available and cost less), and by further elucidating the relationship between temperature exposure and API under various conditions. Oxytocin remains the drug of choice for prevention of postpartum hemorrhage, and OIU has been demonstrated to reduce postpartum hemorrhage by half in home deliveries in Ghana 8 . The data from this simulation study provide some guidance to program managers as to how this effective intervention might be rolled out at scale and how oxytocin could be used at peripheral health facilities without cold-chain capacity.…”
Section: Resultsmentioning
confidence: 92%
“…We recently completed a cluster-randomized trial of the effect of prophylactic use of Oxytocin-in-Uniject (OIU) on postpartum hemorrhage among home deliveries, which found that OIU reduced postpartum hemorrhage by half in home deliveries in Ghana 7 , 8 . OIU is a prefilled, sterile, non-reusable injection device with a single, 10 IU dose of oxytocin.…”
Section: Introductionmentioning
confidence: 99%
“…The product attributes have been tested to ensure that they meet the need at both the community and higher levels of health service. A recent trial in Ghana demonstrated the feasibility at the community level of home delivery for prevention and early treatment 10 , 11 . Thus, the clinical use pathway has largely been followed, even though in some countries, medical associations have objected to policies that would allow for task shifting of oxytocin administration to community health care workers.…”
Section: Case Studies From Institutional Marketsmentioning
confidence: 99%
“…The reproductive health-related trials include comparative evaluation of misoprostol versus manual vacuum aspiration (MVA) for managing incomplete abortion, 62 studies on the effect of extending oxytocin use in the community on prevention of maternal mortality due to post-partum haemorrhage, 67,68 and the effect of different caesarean section surgical techniques on maternal morbidity, mortality and other outcomes. 69 Notable among recent trials is a study that evaluated home visits as a strategy to improve neonatal survival, 65 within which was nested trial which showed that home visits also influenced uptake of skin-to-skin care among low birth-weight infants in rural areas and on neonatal survival.…”
Section: Clinical Trials 2010-2014mentioning
confidence: 99%